Kinerja Organisasi Dalam Pelayanan Pembuatan Kartu Tanda Penduduk Elektronik (KTP-el) Di Kantor Kecamatan Nogosari Kabupaten Boyolali - Saputro, Rohmad Dwi Errin (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2020)
Strategic Boyolali Regency conducts Integrated District Administrative Services, abbreviated as PATEN, that is, conducting administrative services carried out at the local District Office starting from the request to the issuance of documents by submitting the required documents. The purpose of this research is to describe & analyze the performance of organizations in providing services for making Electronic Resident Identity Cards (KTP-el) in the Nogosari District Office in Boyolali Regency. This research uses Agus Dwiyanto Performance Indicator Productivity, Service Quality, Responsiveness, Responsibility, Accountability. Primary and secondary data types. Data collection techniques are interviews, observation, documentation. Descriptive qualitative analysis method. Data analysis Data collection, data condensation, data presentation, conclusion drawing and verification. The results of the Productivity indicators and presponsiveness were good, Service Quality, Responsiveness and Accountability were not good. Suggestions, Service Quality for review, feasibility improvement, and additional facilities and infrastructure. Responsiveness of service providers increases discipline, courtesy, and hospitality. Accountability provides a guarantee of the time from 6 months to 12 months, but if the documents are 12 months before the documents are ready. so, then the service provider providesninformationntonthenapplicant. Keywords: Organizational Performance, Services, Electronic Identity Cards (KTP-el)